2018
DOI: 10.1177/1120672117746931
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure variation by pneumatic tonometer before and after phacoemulsification

Abstract: We conclude that the cataract surgery is related to the reduction of intraocular pressure in the postoperative period and this reduction is more influenced by its preoperative value. Other studies of high epidemiological impact are needed, which may corroborate that the cataract surgery could directly influence intraocular pressure variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the present study, using the pneumatic tonometer, it was evidenced that the IOP values were significantly reduced after isolated cataract surgery and combined surgery in the short and medium term, when compared with the preoperative measurements. Some studies 36 , 37 have already shown a reduction in IOP in a short period of time in isolated cataract, as well as a good concordance between the calibration of pneumatic tonometry and Goldmann’s applanation tonometry. We believe that in the near future, with technological improvement, new studies will be able to analyze this pressure behavior with better accuracy, in relation to the measurement of IOP through pneumatic tonometry.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, using the pneumatic tonometer, it was evidenced that the IOP values were significantly reduced after isolated cataract surgery and combined surgery in the short and medium term, when compared with the preoperative measurements. Some studies 36 , 37 have already shown a reduction in IOP in a short period of time in isolated cataract, as well as a good concordance between the calibration of pneumatic tonometry and Goldmann’s applanation tonometry. We believe that in the near future, with technological improvement, new studies will be able to analyze this pressure behavior with better accuracy, in relation to the measurement of IOP through pneumatic tonometry.…”
Section: Discussionmentioning
confidence: 80%
“…The significant negative contribution of age to the follow-up IOP may be attributable to the reduced production of aqueous humor with age, as supported by the majority of related studies in Asia [ 33 ], whereas contrasting results have been obtained in non-Asian studies [ 34 ]. Furthermore, preoperative IOP has long been regarded as a reliable predictor of postoperative IOP in previous studies [ 35 ].…”
Section: Discussionmentioning
confidence: 99%